2001
DOI: 10.1055/s-2001-14210
|View full text |Cite
|
Sign up to set email alerts
|

Erkrankungen an Malaria in Deutschland 1998/99 - Ergebnisse der Einzelfallerhebungen des Robert-Koch-Institutes

Abstract: Malaria is a common imported infectious disease in Germany. A total of 931 cases of malaria were reported in Germany in 1999 (1998: 1,008 cases). Most of the infected patients were 24-45 years of age. Eighty per cent of the cases acquired infection in Africa, in Asia (8.5%) and in Central and South America (5%). Plasmodium falciparum accounted for the largest number of cases (80%) followed by Plasmodium vivax (12%). In 1999 60% of all malaria cases were Germans. Most of them travelled for holidays or study pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…However, it should be noted that we did not perform systematic risk factor analyses to study the effects of receipt of chemoprophylaxis and sex. We found that the case-fatality rate and the risk of developing severe disease in general increase with age, which is basically consistent with the findings from previous unadjusted or less-extensive analyses [3][4][5][6][7][8][9][10][11], although a quantitative comparison of the findings is impossible to perform because of methodological differences between analyses. To our knowledge, the effect of age on the occurrence of cerebral complications has not previously been analyzed separately in nonimmune patients, although cerebral malaria has been reported as a manifestation of severe disease in previous studies [4,5,7].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, it should be noted that we did not perform systematic risk factor analyses to study the effects of receipt of chemoprophylaxis and sex. We found that the case-fatality rate and the risk of developing severe disease in general increase with age, which is basically consistent with the findings from previous unadjusted or less-extensive analyses [3][4][5][6][7][8][9][10][11], although a quantitative comparison of the findings is impossible to perform because of methodological differences between analyses. To our knowledge, the effect of age on the occurrence of cerebral complications has not previously been analyzed separately in nonimmune patients, although cerebral malaria has been reported as a manifestation of severe disease in previous studies [4,5,7].…”
Section: Discussionsupporting
confidence: 89%
“…Several investigations have indicated that older age is a risk factor for severe [3][4][5][6][7] or fatal falciparum malaria [3,4,[7][8][9][10][11] in nonimmune patients. However, because severe malaria is a rare finding when patients are treated in a timely manner, and because elderly patients account only for a minor fraction of nonimmune patients with malaria, previous analyses were considerably impaired by limited sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1999, 61% of patients had not taken chemoprophylaxis at all while travelling abroad. Improving prophylactic measures is the only way to reduce the incidence of malaria cases in Germany (Schoneberg et al, 2001). Unfortunately, compliance and correct use of prophylactic drugs is regret-tably low (not only among German travelers but among those of many countries); Harms et al (2002) found that among the patients at a travel medicine clinic in Berlin, only 34% of the returnees from malaria-endemic areas had taken chemoprophylaxis.…”
Section: Germanymentioning
confidence: 99%
“…Die Gruppe der Fachvertreter der Epidemiologie bilden die folgenden Autoren -wobei es hierbei große Überschneidungen mit der Fachvertretergruppe der Sozialmediziner gibt: Bergmann [107], Fock [108], Haberland [109], John [110], Schöneberg [111] und Tischer [112].…”
Section: Introductionunclassified